Air contamination inside an actual operating room due to ultrafine particles: An experimental-numerical thermo-fluid dynamic study. (15th March 2021) - Massarotti, Nicola; Mauro, Alessandro; Mohamed, Salahudeen; Romano, Mario R.
Abstract: Hospital Operating Rooms (ORs) are working spaces which demand an utmost clean air environment for enhancing both the safety and the comfort conditions of medical staff and patients, in order to reduce the risk of post-operative complications. In this context, an integrated experimental-numerical thermo-fluid dynamic study has been carried out in the present work, to investigate air contamination due to UltraFine Particles (UFPs) inside an actual, but unoccupied, OR, equipped with a laminar air flow system, located near Milan in Northern Italy. The UFPs considered in the present study are geometrically representative of surgical smoke and SARS-CoV, SARS-CoV-2 (COVID-19) virus particles. The flow and thermal fields in the OR have been calculated by using the Realizable k-ε turbulence model. A transient passive scalar species transport equation, based on the drift flux model, has been implemented along with the particle deposition boundary conditions at the OR walls, to analyze the UFPs concentration within the OR. The numerical model has been used, after validation against experimental data, to reproduce the quantities of interest in the OR. Moreover, type A and type B uncertainties have been associated to the experimental measurements. The velocity and temperature fields in the OR, obtained from both the numerical and experimental analysis, are compliant to the technical standards. A good agreement is observed between experimental and numerical results, in terms of velocity, temperature and UFPs concentration. A time of 19 min to completely evacuate UFPs from the OR has been obtained from both experimental and numerical analysis, with a deviation smaller than 2% between the results. Highlights: An integrated experimental-numerical study is carried out to investigate air contamination inside a real Operating Room (OR). A 3D thermo-fluid dynamic model has been developed to simulate the OR equipped with a Laminar Air Flow (LAF) system. The contaminant Ultrafine Particles (UFPs) considered are representative of SARS-CoV, SARS-CoV2 (COVID-19) virus particles. The downward airflow from the LAF system allows an effective evacuation of UFPs from the sterile zone. The total particle loss rate of UFPs is dominated by the Air Exchange Rate, much larger than the surface deposition rate. A time of 19 minutes to completely evacuate the UFPs from the OR is obtained from the experimental and numerical analysis.